A certain slant of light - Thayer, Cynthia A. (New York : St. Martin's Press, 2000)
After losing his wife in a tragic fire, Peter has become a hermit on the coast of Maine, sheering sheep and gardening to survive but a runaway pregnant wife will change his life when she shows up on his doorstep.
Maine author. Thayer lives in Gouldsboro.
Keywords: Pregnant women -- Fiction; Runaway wives -- Fiction; Friendship -- Fiction; Widowers -- Fiction; Psychological fiction; Maine -- Fiction